Implant-Retained Obturator for an Edentulous Patient with a Hemimaxillectomy Defect Complicated with Microstomia - Pravinkumar G. Patil; Smita Nimbalkar-Patil (Hindawi Limited, 2016)
Patient. A 68-year-old man was operated on for squamous cell carcinoma (T3N3M0) of the maxilla creating the hemimaxillary surgical defect on right side. The remaining arch was completely edentulous. There was remarkable limitation in the oral opening with reduced perimeter of the oral cavity due to radiation and surgical scar contracture. This article describes prosthetic rehabilitation by modifying the design of the obturator and achieving the retention with dental implant. Discussion. Severe limitation in the oral opening may occur in clinical situations following the postsurgical management of oral and maxillofacial defects. The prosthetic rehabilitation of the surgical defect in such patients becomes a challenging task due to limited access to the oral cavity. This challenge becomes even more difficult if the patient is edentulous and there are no teeth to gain the retention, stability, and support. Conclusion. In severe microstomia prosthesis insertion and removal can be achieved with modification of the maximum width of the prosthesis. Dental implant retention is useful treatment option in edentulous patients with maxillary surgical defect provided that sufficient bone volume and accessibility are there for implant placement.